Master of Professional Studies in Agriculture and Life Sciences offered through the Field of Food Science and Technology at Cornell University: A Model for the Development of a Course‐Based Graduate Degree in Food Science and Technology. Issue 1 (January 2015) - Weller, Daniel; Robbins, Janette; Elmore, Andrea; Wiedmann, Martin
Abstract The shortage of highly qualified graduates with advanced training in food science is a pressing problem facing government agencies and the food industry. This has created a need to recruit and train food scientists at the graduate level. However, most graduate level programs are research‐based and do not meet the needs of many students. The College of Agriculture and Life Sciences at Cornell Univ. has a Master of Professional Studies Program in Agriculture and Life Sciences (MPS‐ALS), which is offered through the Field of Food Science and Technology (FFST), as an alternative to research‐based masters and doctoral degrees. Although the MPS‐ALS program began in the 1970s, the FFST did not take an active role in recruiting students or tracking alumni until 2000. From 2000 to 2013, a total of 56 students, representing an internationally and academically diverse student body, have received MPS‐ALS degrees through the FFST. In May and August 2013, alumni were asked, via e‐mail, to complete an online survey to assess the long‐term impact of the MPS‐ALS program on their career success. The results of the survey indicate that the MPS‐ALS program at Cornell Univ. is a strong program that attracts excellent candidates from a variety of undergraduate fields. Program alumni have been very successful in obtaining full‐time employment, graduate positions and internships, and are highly satisfied with the program. The MPS‐ALS offered through the FFST at Cornell Univ. is a model for the development of course‐based graduate programs that seek to increase the supply of and meet the demand for trained professionals in food science.